Evaluation of Some Botanicals against Callosobruchus chinensis L. Infesting Stored Chickpea Seeds and Bio-Chemical Analysis of Used Botanicals - Mounika, Tumma; Sahoo, S. K.; Chakraborty, D. (International Journal of Bio-resource and Stress Management, 2021)
A study was carried out to evaluate the bio-efficacy of some botanicals against Callosobruchus chinensis L. in stored chickpea (Variety: Anuradha) in the year 2018–20. Different botanicals like Neem (Azadirachta indica), Melia (Melia azedarach), Datura (Datura stramonium) and Tulsi (Ocimum sanctum) were used. Among all the botanicals Neem leaf powder @ 6% performed better with minimum egg laying (64 eggs 5 females-1) compared to the other botanicals except the standard check with Deltamethrin @ 0.04%. Thereafter, 6% Melia leaf powder and 8% Datura leaf powder recorded 87.50 eggs 5 females-1 and 91.25 eggs 5 females-1, respectively. With regard to adult mortality, the best result was also obtained from the treatment Neem leaf powder @6% with 96.67% mortality in 5th day. Following the same trend, 6% Melia leaf powder and 8% Datura leaf powder exhibited 90% and 83.33% adult mortality, respectively, in 5th day. The estimation of total phenols and total antioxidants (IC-50) contents in Neem leaf powder (345.69 mg g-1 and 207.77 μg ml-1), Melia leaf powder (273.40 mg g-1 and 383.68 μg ml-1) and Datura Leaf Powder (213.62 mg g-1 and 405.77 μg ml-1) also confirms the findings of the bio-efficacy trial of the botanicals. Tulsi leaf powder @5% was least efficacious both in terms of egg laying by the females as well as adult mortality. These botanicals are locally available, economic, bio-degradable and safe to the environment. Therefore, they may be fitted in the Integrated Pest Management strategies against stored grain pests as seed protectants.